2020
DOI: 10.1029/2020ja027794
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Nominal Thickness and Variability of the Magnetodisc Current Sheet at Saturn

Abstract: The thickness and variability of the Saturnian magnetodisc current sheet is investigated using the Cassini magnetometer data set. Cassini performed 66 fast, steep crossings of the equatorial current sheet where a clear signature in the magnetic field data allowed for a direct determination of its thickness and the offset of its center. The average, or nominal, current sheet half-thickness is 1.3 R S , where R S is the equatorial radius of Saturn, equal to 60,268 km. This is thinner than previously calculated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 70 publications
4
32
0
Order By: Relevance
“…Carbary (2019) determined averaged empirical models of the thickness of the ring current from Cassini's magnetic field data. We find that the Staniland et al (2020) ring current agrees with the more intense ring current region determined by Carbary (2019). The maximum thickness of the ring current detected here on the proximal Revs is slightly smaller than the outer boundary region presented by Carbary (2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Carbary (2019) determined averaged empirical models of the thickness of the ring current from Cassini's magnetic field data. We find that the Staniland et al (2020) ring current agrees with the more intense ring current region determined by Carbary (2019). The maximum thickness of the ring current detected here on the proximal Revs is slightly smaller than the outer boundary region presented by Carbary (2019).…”
Section: Discussionsupporting
confidence: 83%
“…This resulted in a modelled ring current with a mean value of <D> = 3.21 ± 0.62 R s . This is identical within errors to our mean thickness reported in Figure 13, meaning that the discrepancy between the thickness of the ring current found in this study compared to that reported by Staniland et al (2020), cannot be explained by the initial assumptions made in our ring current modelling.…”
Section: Comparison Withsupporting
confidence: 89%
“…Our results are shown as white lines and colored circles with white edges. The 47 thickness measurements from Staniland et al (2020), presented in Figure 13 as black diamonds, are shown in Figure 2b as black lines, also symmetrically extended to either side of the center of the current sheet. Studying Figure 2b we can see that both sets of results show some features of similarity in the decrease of ring current thickness with radial distance.…”
Section: Comparison Withmentioning
confidence: 97%
“…Studying Figure 2b we can see that both sets of results show some features of similarity in the decrease of ring current thickness with radial distance. However, the ring current thicknesses from Staniland et al (2020)…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation